EVALUATION OF Bacillus thuringiensis FROM DIFFERENT HABITATS FOR LETHALITY AGAINST LARVAE OF SOME SPECIES OF MOSQUITO - Zubairu, Maimuna; Zubairu, Abdulaziz; Rabiu, Karima M.; Abdu, Fatima; Uthman, Hajara A. (FUDMA JOURNAL OF SCIENCES, 2022)
This work was aimed at evaluating the lethality effects of Bacillus thuringiensis isolated from different habitats against larvae of some species of mosquito. The isolated and identified microorganism  from the different sampling sites were subjected to bioassay against different species of mosquito larvae at 0, 8.0 Ã— 109, 1.6 Ã— 1010, 3.2 Ã— 1010, 6.4 Ã— 1010, and 7.2 Ã— 1010 cells/ ml. The result of the study revealed that B. thuringiensis isolated from compost manure had the highest bioactivity of 100% mortality against all the three species of mosquito larvae used in this work at the concentration of 3.2 Ã— 1010 cells / ml while those isolated from garden soil, refuse, animal residue and dry leaf residue gave 100% mortality at 6.4 Ã— 109 cells / ml against the three species of mosquito larvae with the exception of that isolated from animal residue which gave 95% mortality against aedes larvae at 6.4 Ã— 1010 cells/mls. Analysis of variance at P < 0.05 revealed a significant difference in activity of B. thuringiensis isolated against mosquito larvae belonging to different species. This indicated that Bacillus thuringiensis had higher lethal activities against culex and anopheles larvae than aedes larva.
Keywords: Bacillus thuringiensis; Bioactivity; Mosquito; Larvae; Mortality